An evaluation on personal finance web system for university students / Nor Azzyati Hashim, Nor Faridah Bani Omar and Romiza Md Nor - Hashim, Nor Azzyati; Bani Omar, Nor Faridah; Md Nor, Romiza (UiTM Cawangan Perlis, 2016)
The exposure of personal finance literacy among youth has started to get further attention worldwide on account of economic instability and rising cost of living. Knowing about personal finance as early as possible becomes important because being fit in money management is one of the factors that lead for better lifestyle and early financial freedom. A web-based system in a university setting is expected to help university students take advantage of this opportunity. This paper investigates the benefits of a web system called e-Personal Finance (e-PF) for bachelor degree students in Universiti Teknologi MARA (UiTM) Perlis Branch. e-PF is composed of three main sections; Financial Test, Budget Planner and Finance Calculator. Evaluation for this web system using usability testing involved 50 bachelor degree students from seven faculties and two finance lecturers cooperated to give their expert point of view and opinion. From the findings, it is discovered that e-PF can help students to improve their knowledge and attitude about personal finance. As a conclusion, e-Personal Finance is found to be relevant in becoming one of education medium to assist university students in personal finance literacy, planning and management.